(untitled) (Research, Society and Development, 2021)
The research aimed to know the performance of PEF through the perception of users and workers in a CAPS of Recife / PE. It is an exploratory research, case study with a qualitative approach. Two PEF, four users and two CAPS workers participated in the study. We chose to work with the semi-structured interview method. The collected data were verified through Content Analysis. After the analysis four topics emerged: group movement in CAPS, body and use of psychotropic drugs, interprofessional work and PEF exit from CAPS. PEF’s performance in CAPS is seen as a valuable therapeutic resource for users. It is through body practices that greater body knowledge, user integration with the environment and social reintegration is promoted. Therefore, the departure of PEF led to a loss to mental health devices and break the therapeutic process of users.